A preliminary study on waste marble powder-based alkali-activated binders. (16th May 2023) - Liu, Bing; Geng, Songyuan; Ye, Junpeng; Liu, Xiaoyan; Lin, Weixin; Wu, Shihao; Qian, Kai
Highlights: WMP can be used alone as a precursor to produce alkali-activated binder. Na2 O greatly impact on strength, and modulus on setting time of WMP-based binder. Higher pre-curing temp & high-temp curing time boost early strength, not late. Sealed curing method promotes steady strength growth in WMP-based binder. Abstract: Marble, as a widely used building decoration material, produces a significant amount of waste marble powder (WMP) during processing. To investigate the potential of WMP as a precursor in the preparation of alkali-activated binders, this paper uses WMP as the only precursor and conducts a series of macroscopic mechanical and microscopic characterization tests. The variables included the alkali activator modulus (Ms), Na2 O dosage, and curing conditions. The results showed that increasing the Na2 O dosage shortened the setting time of the binders, reduced the fluidity, and improved the strength. With the increase in the modulus of the alkali activator, the binder setting time was prolonged, the fluidity first increased and then decreased, and the strength decreased. Increasing the precuring temperature and prolonging the high-temperature curing time was beneficial to developing early strength. Sealed curing was more favorable for stable strength development than standard curing. Scanning electron microscopy (SEM), Energy dispersive spectroscopy (EDS), X-ray diffraction (XRD), Thermogravimetric analysis (TGA), and Fourier transform infrared (FTIR) characterization tests revealed that the dissolution of WMP occurred in the alkali activator, and the hydration products contained carbonate, C-S-H, N-C-S-H, and other substances. The results of the gray correlation analysis showed that the Na2 O dosage had a greater influence on the binder fluidity than the alkali activator modulus, while the setting time was the opposite. The effects of the four studied factors on the long-term flexural and compressive strengths of the specimens were in the consistent order of Na2 O dosage > alkali activator modulus > precuring temperature > high-temperature curing time.